1962
DOI: 10.1084/jem.115.6.1173
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Chronic Excess Salt Ingestion

Abstract: There is considerable evidence which can be interpreted to indicate a familial trend in human essential hypertension (1-5). A familial disease could be due exclusively to common environmental factors, exclusively to common genetic patterns, or to an interaction of the two.For some years we have been exploring the effects of chronic excess salt ingestion in both man and animals and have brought forward evidence to support the thesis that dietary salt plays an etiologic role in human essential hypertension (6-12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
160
0
1

Year Published

1966
1966
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 592 publications
(164 citation statements)
references
References 13 publications
3
160
0
1
Order By: Relevance
“…In the early 1960s, he turned his attention to studies in the rat, in which he, like Meneely et al, showed that chronic excess salt ingestion leads to sustained hypertension. 6 Taking advantage of the observation that not all rats responded to salt with similar changes in blood pressure and cognizant of the data suggesting genetic influences on blood pressure in humans, Dahl et al 7 s were able to selectively breed rats for susceptibility (S rats) or resistance (R rats) to the hypertensive effects of high salt (8% NaCl) diet. After only three generations of selective breeding, the S and R lines were clearly separated.…”
Section: Selective Breedingmentioning
confidence: 99%
“…In the early 1960s, he turned his attention to studies in the rat, in which he, like Meneely et al, showed that chronic excess salt ingestion leads to sustained hypertension. 6 Taking advantage of the observation that not all rats responded to salt with similar changes in blood pressure and cognizant of the data suggesting genetic influences on blood pressure in humans, Dahl et al 7 s were able to selectively breed rats for susceptibility (S rats) or resistance (R rats) to the hypertensive effects of high salt (8% NaCl) diet. After only three generations of selective breeding, the S and R lines were clearly separated.…”
Section: Selective Breedingmentioning
confidence: 99%
“…The current analysis uses the estimates of genetic variance according to criteria established by Christian et al 1 " The equality of total variance was evaluated by an F' test. When the total variance of MZ and DZ twins was equal, the presence of genetic variance was tested using the F ratio (Within DZ/Within MZ).…”
Section: Studies In Twinsmentioning
confidence: 99%
“…This suggests that some individuals will respond to dietary sodium intake with an increase in blood pressure (BP) while others are relatively resistant to the pro-hypertensive effects of sodium. Indeed, Dahl et al 4 have been able, …”
mentioning
confidence: 98%
“…This suggests that some individuals will respond to dietary sodium intake with an increase in blood pressure (BP) while others are relatively resistant to the pro-hypertensive effects of sodium. Indeed, Dahl et al 4 have been able, through selective inbreeding, to produce genetically salt-sensitive and salt-resistant strains of rats. At present, other than through the clue provided by a positive family history, there are no ways to identify individuals with potentially salt-sensitive hypertension who might benefit from early dietary counseling.…”
mentioning
confidence: 99%